Nitrous oxide improves cardiovascular, respiratory, and thermal stability during prolonged isoflurane anesthesia in juvenile guinea pigs. Issue 1 (4th February 2021) - Sixtus, Ryan P.; Gray, Clint; Berry, Mary J.; Dyson, Rebecca M.
Abstract: Anesthesia is frequently used to facilitate physiological monitoring during interventional animal studies. However, its use may induce cardiovascular (central and peripheral), respiratory, and thermoregulatory depression, confounding results in anesthetized animals. Despite the wide utility of guinea pigs as a translational platform, anesthetic protocols remain unstandardized for extended physiological studies in this species. Therefore, optimizing an anesthetic protocol that balances stable anesthesia with intact cardiorespiratory and metabolic function is crucial. To achieve this, 12 age and sex‐matched juvenile Dunkin Hartley guinea pigs underwent extended anesthesia (≤150 min) with either (a) isoflurane (ISO: 1.5%), or (b) isoflurane + N2 O (ISO+ N2 O: 0.8% +70%), in this randomized cross‐over designed study. Cardiovascular (HR, SBP, peripheral microvascular blood flow), respiratory (respiratory rate, SpO2 ), and thermal (Tre and Tsk ) measures were recorded continuously throughout anesthesia. Blood gas measures pre‐ and post‐ anesthesia were performed. Incorporation of 70% N2 O allowed for significant reductions in isoflurane (to 0.8%) while maintaining an effective anesthetic depth for prolonged noninvasive physiological examination in guinea pigs. ISO+N2 O maintained heart rate, peripheral blood flow, respiratory rate, and thermoregulatory function at levels closest to those of conscious animals, especially in females; however, it did not fully rescue anesthesia‐induced hypotension. These results suggest that for studies requiring prolonged physiological examination (≤150 min) in guinea pigs, 0.8% isoflurane with a 70% N2 O adjuvant provides adequate anesthesia, while minimizing associated cardiorespiratory depression. The preservation of cardiorespiratory status is most marked throughout the first hour of anesthesia. Abstract : Comprehensive physiological, pharmacological and imaging studies frequently use inhalational anaesthesia to maintain compliant animal subjects. Here, we describe an optimised anaesthetic protocol (0.8% isoflurane + 70% nitrous oxide) for extended minimally‐invasive physiological monitoring in guinea pigs, increasing the translational capacity of the guinea pig as a model for understanding human (patho)physiology.